Modified Si-Ni-San Decoction Ameliorates Central Fatigue by Improving Mitochondrial Biogenesis in the Rat Hippocampus. (29th July 2018) - Han, Chenxia; Li, Feng; Liu, Yan; Ma, Jie; Yu, Xue; Wu, Xiumei; Zhang, Weiyue; Li, Danxi; Chen, Dou; Dai, Ning; Lin, Bingqi; Wu, Fengzhi; et al.
Abstract : The traditional Chinese medicine (TCM) decoction Si-Ni-San (SNS) has been utilised for millennia to improve physiological coordination of the functions of the liver and spleen, which are regarded as the main pathological organs of central fatigue in TCM. This study evaluates the effect of a modified SNS (MSNS) formula on central fatigue in rats and explores molecular changes associated with hippocampal mitochondrial biogenesis. Central fatigue was induced through a 21-day sleep deprivation protocol. We assessed MSNS's effects on behaviour, blood and liver biomarkers, and mitochondrial ultrastructure. We found that MSNS could reverse various signs of central fatigue such as its effects on hippocampal gene and protein expression levels of sirtuin 1 (SIRT1), peroxisome proliferator-activated receptor gamma coactivator-1 α (PGC-1 α ), and nuclear respiratory factor 1 (NRF1). We also observed evidence of MSNS decreasing central fatigue, such as decreasing creatine kinase activity, decreasing levels of malondialdehyde and blood urea nitrogen, increasing lactate dehydrogenase and superoxide dismutase activities, increasing mitochondrial DNA copy number, and reversing mitochondrial ultrastructure changes. These findings suggest that MSNS can ameliorate central fatigue and that its molecular mechanism involves mitochondrial biogenesis enhancement mediated by hippocampal SIRT1, PGC-1 α, and NRF1.